L’«Elettra» (1903) di Hugo von Hofmannsthal tra Sofocle e D’Annunzio (Studia austriaca, 2013)
Hofmannsthal’s play «Elektra» aroused controversial reactions when it appeared in 1903: on the one hand, great enthusiasm, on the other hand irritation and hostility towards its undoubted “modernity”. This essay highlights some scarcely known aspects of the context in which the play came into being, focusing particularly on its relationship with the Sophoclean subtext and Hofmannsthal’s coeval and later poetical works, as well as with D’Annunzio’s drama «La città morta», performed in Vienna in 1902 and 1903 with Eleonora Duse in the main role.